Projeto térmico de trocadores de calor resfriados a ar - Silva, Diomedes Cesário da (1980)
The scarcity and the treatment costs of the water cooling, in the petroleum and petrochemical industries, are increasing the use of the air cooled heat exchangers. Exchangers designing usualy utilize the estimate and global methods. This paper shows these methods and presents a new approach for this design, called "stepping method'', which consider the tube bundle divided in small segments and utilizing the computer recourses, excutes the calculations starting from the exit process fluid temperature, inlet air temperature and equipment dimensions. The stepping method is more rigorous and permits to consider in the calculations the nonuniformities in the facial air velocities, ~hysical properties variations with temperature and change in tube side flow. ln the equipments analysed, operating with various fluids like pioor oil,light gasoil, light naphta, kerosene, are verified that the fluids whose properties change greatly with the temperature specially the viscosity the results obtained by the two methods present great differences. This discreppance is still greater if a nonuniform air velocity distribution is used. In situations where the process fluid presents a variation in the pattern flow the duties difference is also considerable. The results obtained are practically equals, when the fluid is water, even for nonuniform air distribution. The stepping method is more rigorous and make possible a visualization of the heat transfer and pressure drop along tube bundle, being then a powerful method for the designing and performance analysis of the air cooled heat exchangers.